EFFECT OF FIRE-INDUCED PROGRESSIVE FAILURE ON THE PERFORMANCE OF 5-STORY STEEL BENDING FRAME BUILDINGS USING INCREMENTAL NONLINEAR DYNAMIC ANALYSIS - Mojtaba Motahari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research has studied the fire-induced progressive failure in steel structures, which has been less studied in Iran up to now. To this aim, three-dimensional and two-dimensional models statistical tools such as mean and standard deviation as well as engineering software were applied in the analysis of data to analyze the time history of the structure. To make the results reliable, computational software such as SiesmoStruct and Etabs were applied, and to extract the probability of some cases from the IDA analysis outputs, diagrams called fragility curves were used, and finally, effective solutions were suggested. In this research, the vulnerability of the structure under progressive failure was studied in two steps in a 5-story steel model and using fragility curves, the probability of failure of each of them were determined in the form of fragility curves for CP performance levels. Finally, comparing the fragility curves, it can be realized that the probability of structural failure is lower for a more intact structure with a lower height than for tall structures. Therefore, structures with high ductility compared to other cases, have less annual damage and structures with low ductility can be considered as the next option. Of course, it is essential to explain that the cost of construction of each structure should also be considered by contractors as the cost of construction of a structure with high ductility is much higher than other structures.